Salmonella enterica Control in Stick Carrots Through Incorporation of Coriander Seeds Essential Oil in Sustainable Washing Treatments - Pellegrini, Marika; Rossi, Chiara; Palmieri, Sara; Maggio, Francesca; Chaves-López, Clemencia; Lo Sterzo, Claudio; Paparella, Antonello; De Medici, Dario; Ricci, Antonella; Serio, Annalisa (Frontiers in Sustainable Food Systems, 2020)
Chemical disinfectants represent one of the commonly used practice in minimally processed vegetables food-chain. However, the scarce safety and sustainability of these agents force food industry to move toward more sustainable “green washing solutions.” Among the latter, while the application of plant derivates for the control of several pathogens is already well-known, the potential anti-Salmonella activity of Coriandrum sativum seeds derivates is still unexplored and was therefore investigated in this study. In detail, Minimal Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC) of different coriander seed derivates (i.e., essential oil, hydrosol, and ethanolic extract) were determined by broth dilution against six Salmonella enterica strains isolated from fresh and minimally processed fruits and vegetables. Only the essential oil (EO) was effective in vitro with strain-dependent results. In addition, when mixed in co-culture, the strains were more sensitive to the essential oil treatment. Chemical investigations allowed to define (s)-(+)-linalool as major compound in the essential oil, and to underline interesting phenolic content with correlated antioxidant capacity. A cocktail of three strains of different serovars was selected and employed for a preliminary in situ trial on stick carrots. The obtained results allowed to establish that the application of coriander seed EO at concentrations of 5 μL mL−1 was able to reduce and contain the growth of the Salmonella cocktail up to 24 h at 10°C. Good sensory evaluation results were obtained by applying this EO concentration as washing treatment, especially in terms of color parameter. Further studies should be undertaken to emphasize the upstream activity, improving the formulation or exploiting a combined effect with other sanitizers or treatments (e.g., physical treatments). The present study contributes to the knowledge on coriander derivates activity against Salmonella spp. and on the potential application as sustainable washing treatment in removing this pathogen from fresh cut carrots.